Navigating Risk: Perspectives of Semester 3 Cadets at the Maritime Institute Jakarta on Risk Assessment Approaches for Offshore Structures - Marudut Bernadtua Simanjuntak (LPPM Politeknik Pratama, 2023)
This study delves into the perspectives of 240 Semester 3 cadets at the Maritime Institute Jakarta (STIP Jakarta) regarding Risk Assessment Approaches for Offshore Structures. Employing a qualitative descriptive approach, the research unfolds over three semesters, encompassing approximately 18 months of academic, mental, and professional preparation for internships in the maritime industry. The cadets, hailing from diverse regions across Indonesia, undergo an international program at STIP Jakarta, necessitating a mastery of English communication in line with International Maritime Education standards. The research navigates through the complexities of maritime education, focusing on academic preparedness, motivations, language proficiency, and perspectives on risk assessment. Academic preparedness reveals a commendable level among cadets, yet the identification of lower preparedness levels signals potential areas for curriculum refinement. Intrinsic motivation, predominantly rooted in a passion for the maritime profession, underscores the institute's success in instilling commitment and purpose among cadets. Language proficiency emerges as a critical determinant, with recommendations for targeted language support to bridge proficiency gaps. The qualitative analysis of cadet perspectives on risk assessment unveils themes of practical application, interdisciplinary understanding, and the pivotal role of language proficiency. These themes advocate for a paradigm shift in teaching methodologies and curriculum design to align with industry demands. The research concludes with implications for curriculum refinement, passion cultivation, language support programs, practical integration, interdisciplinary collaborations, and a continuous feedback mechanism. These recommendations serve as a blueprint for STIP Jakarta's evolution, ensuring the institute remains at the forefront of excellence, innovation, and global relevance in maritime education.